In vivo models for the evaluation of the osteogenic potency of bone substitutes seeded with mesenchymal stem cells of human origin: a concise review - Westhauser, Fabian; Reible, Bruno; Moghaddam-Alvandi, Arash (Tissue engineering. Part C, Methods, 2017)
Research concerning bone substitutes is one of the most challenging fields in orthopedic research and has a high clinical relevance, especially since the currently available bone substitutes are limited in their osteostimulative capabilities. In vitro models for the evaluation of the properties of bone substitutes allow the use of human mesenchymal stem cells (hMSCs) seeded onto scaffolds, but suffer from the lack of a physiological environment for those cells. Most in vivo models include the use of non-hMSC and are therefore lacking in clinical relevance. To overcome these issues, in vivo models were created that allow the evaluation of hMSC-seeded bone substitutes, combining the advantages of the use of human cells with the physiological conditions of an organism in vivo. In brief, models usually aim for bone formation in immunocompromised rodents. The subcutaneous implantation of scaffolds is most widely performed, showing low complication rates along with good results, but suffering from inferior vascularization of the implants and the absence of the realistic structural and mechanical conditions of bone. Orthotopic implantation, for example in calvarian or long bone defects, provides the most appropriate surrounding for hMSC-seeded scaffolds. However, parallel host-induced bone formation is a major limitation. This review summarizes in vivo models for the evaluation of the osteogenic potency of bone substitutes seeded with mesenchymal stem cells of human origin.
Gesehen am 29.10.2018